Asymmetric Impact of Exchange Rate and Industrial Production on Indonesian Agricultural Exports - Elfiana; Fachrurrozi, Kamal (Jurnal Ekonomi Pembangunan, 2025)
The agricultural sector plays a pivotal role in the economies of agrarian nations. This study investigates the asymmetric impact of both the exchange rate and the industrial production index on Indonesian agricultural exports from January 2010 to August 2023. Employing the Non-Linear Autoregressive Distributed Lag (NARDL) model, we captured the nuanced asymmetric effects of these predictors. Our findings reveal that both positive (depreciation) and negative (appreciation) exchange rate asymmetries significantly influence agricultural exports in the long run. The exchange rate multiplier effect suggests that depreciation will lead to increased agricultural exports in the short run, partly due to future exchange rate interventions. Furthermore, a positive industrial production index consistently and significantly impacts agricultural exports in both the short and long run, demonstrating steady growth over time. These findings carry important policy implications. Policymakers should consider these findings when controlling and maintaining the exchange rate at an optimal level. Policymakers should prioritize the development and strengthening of the industrial sector to enhance agricultural export performance.